Assessing the risk and cost of foreign currency denominated sovereign debt in developing countries - Alberto Isgut (University of Athens, Department of Economics, International Economics and Development Laboratory (IEDL), 2025)
The risks posed by issuing debt denominated in a foreign currency are well understood: if the domestic currency depreciates, the local currency cost of servicing such debt will increase. But what has been the recent experience of developing countries? This paper provides a quantitative assessment of the additional cost of servicing foreign currency denominate debt using both data on individual sovereign and subnational bonds and data from the World bank's International Debt Statistics database. The paper also explores whether such additional costs, which are due to depreciation of the exchange rate, have an adverse effect on fiscal space.
Keywords: F34; H63; E62; G15; O23; 330; Sovereign debt; developing countries; foreign currency denominated debt; currency risk; fiscal space